Hydrogen Spillover‐Promoted Hydrogen Evolution onto Copper. Issue 4 (19th January 2023) - Xing, Liwen; Liu, Yan; Liu, Yaqi; Wu, Ke; Ji, Yongjun
Abstract: Currently, green hydrogen harvesting from electrochemical water splitting is overly reliant on noble metals with high catalytic activity but low natural abundance and high cost. As one of potential earth‐abundant alternatives, copper, however, displays a poor hydrogen evolving capability, mainly due to inherently a weak hydrogen binding energy (HBE). It poses a substantial restriction to metallic Cu alone serving as primary active sites for high‐performance hydrogen evolution. Thanks to the presence of hydrogen spillover that was often overlooked during the electrocatalysis, the hydrogen evolution in a nonacidic electrolyte can be accelerated by the recombination desorption of adsorbed hydrogen over Cu with a weak HBE. Here, we concisely highlighted this promotion effect of secondary active Cu on electrocatalytic hydrogen evolution and eagerly expected to extend hydrogen spillover effects to the advance of multi‐site electrocatalytic systems. Abstract : Spillover‐Promoted Evolution : Rational design and synthesis of high‐performance hydrogen‐evolving electrocatalysts is of great significance by using cheap and rich base metals like copper. This concept article provides a concise overview of H spillover‐promoted electrocatalytic hydrogen evolution onto Cu surface, making inherently inert materials to be potentially active.